Smart Geopolitics, Dangerous Ideas: Energy security, Ideology, and the Challenges of American Policy in the Persian Gulf - Diego Pagliarulo (European Journal of American Studies)
Both as a superpower and as the West's leading security provider, the US has seen its commitment to the stability of the Gulf region and the preservation of access to its oil supplies increase. US Persian Gulf policy, however, has been shaped not only by pure geopolitical considerations, but also by ideological factors concerning America's status and role in international relations. Until recently, US policy toward the Persian Gulf was distorted by the appeal of America's unchallenged military primacy. Confronted with the contradictions and dilemmas of promoting ideals and protecting the national interest, US policy-makers demonstrated a remarkable penchant for instituting policies that overestimated the potential of America's military power as a tool for creating new political realities and favorable outcomes in the region. Such an approach has proved to be extremely costly and frustrating, while the time seems ripe to explore new strategies. The US should not strive to reshape or control the geopolitics of the Gulf, as both these approaches are unfeasible. The idea of disengagement from the region, moreover, appears delusional even when the implications of the unconventional energy revolution are held into account. Rather, America and its allies should focus their engagement on protecting their interests without becoming part of the region’s sources of instability.